Identification of Novel Mutations in Arabidopsis thaliana DOF 4.2 Coding Gene - Omid Jamshidi Kandjani; Mahdieh Rahbar-Shahrouziasl; Ali Akbar Alizadeh; Maryam Hamzeh-Mivehroud; Siavoush Dastmalchi (Tabriz University of Medical Sciences, 2021)
Purpose: DOF (DNA-binding with One Finger) proteins are plant-specific transcription factors which mediate numerous biological processes. The purpose of the current study is to report new naturally occurring mutations in the gene encoding for one of the members of DOF proteins named DOF 4.2. Methods: The expression of zinc finger domain of DOF 4.2 (DOF 4.2-ZF) was investigated by first synthesis of cDNA library using different parts of Arabidopsis thaliana plant. Then the coding sequence for zinc finger domain of DOF 4.2 protein was prepared using nested PCR experiment and cloned into pGEX-6P-1 expression vector. Finally, the prepared construct was used for protein expression. Furthermore, molecular dynamics (MD) simulation was carried out to predict DNA binding affinity of DOF 4.2-ZF using AMBER package. Results: For the first time a new variant of DOF 4.2-ZF protein with three mutations was detected. One of the mutations is silent while the other two mutations lead to amino acid replacement (S18G) as well as introduction of a stop codon ultimately resulting in a truncated protein production. In order to investigate whether the truncated form is able to recognize DNA binding motif, MD simulations were carried out and the results showed that the chance of binding of DOF 4.2-ZF protein to cognate DNA in its truncated form is very low. Conclusion: The findings demonstrated that the observed mutations adversely affect the DNA binding ability of the truncated form of DOF4.2 if it is expressed in the mutant variant of A. thaliana used in this study.